Decoding tourist satisfaction and loyalty at hotels: a confirmatory factor analytic approach. (25th January 2022) - Adil, Mohd; Nasir, Mohd; Kumar, Mukesh
This study assesses tourists' perceived service quality towards budget hotels. It also examines the inter-relationship between the service quality dimensions, tourist satisfaction and tourist loyalty. A structured questionnaire was employed to survey the tourists who visited and stayed in budget hotels of the selected three states of Northern India. An assessment of common method bias and preliminary descriptive analysis was used to examine the item structure and psychometric properties of the original scale adopted in the current study. Findings reveal that all the dimensions of service quality have a positive influence on tourist satisfaction, therefore hotel managers must monitor and assess their offerings on all the seven key attributes of service quality at regular intervals. This may avoid instances of customer dissatisfaction or moments of frustration and, eventually boosts repeat purchases and positive word of mouth. In addition, hotel management should also pay special attention to the employees' educational eligibility and desired skill during the recruitment process, to better understand tourists' needs and design service which contributes to the tourists' overall experience at budget hotels.